Nicholas Piercey, Four histories about early Dutch football 1910-1920. Constructing discourses. - Michel van Gent (BMGN: Low Countries Historical Review, 2017)
Nicholas Piercey, Four Histories about Early Dutch Football 1910-1920. Constructing Discourses (Londen: UCL Press, 2016, 228 pp., ISBN 978 191 063 478 3).